(untitled) (The Review of Diabetic Studies, 2024)
Diabetes mellitus represents one of the most complex chronic diseases confronting modern healthcare systems, driven by rising global prevalence, increasing therapeutic complexity, and profound social and economic determinants of health. Advances in diabetes care—including continuous glucose monitoring technologies and novel antidiabetic pharmacotherapies such as glucagon-like peptide-1 receptor agonists and sodium-glucose cotransporter-2 inhibitors—have transformed glycemic management but simultaneously increased the need for coordinated, multidisciplinary care. In parallel, growing evidence highlights the decisive influence of social risk factors, including food insecurity, health literacy, housing instability, and medication affordability, on diabetes outcomes. This review examines an integrated primary care model that unites family physicians, nurses, pharmacists, laboratory services, and social service professionals to optimize diabetes management. Emphasis is placed on the clinical integration of continuous glucose monitoring, individualized pharmacotherapy, laboratory-guided decision-making, and systematic social risk assessment. By synthesizing current evidence and care models, this review underscores that modern diabetes management is not solely a biomedical endeavor but a coordinated, patient-centered process requiring clinical, technological, and social alignment.